Anaplastic lymphoma kinase negative anaplastic large cell lymphoma of hard palate as first clinical manifestation of acquired immune deficiency syndrome - Anjali Narwal; Achla Bharti Yadav; Sant Prakash; Shally Gupta (Wolters Kluwer Medknow Publications, 2016)
Anaplastic large cell lymphoma (ALCL) is an uncommon disease, accounting for <5% of all cases of non-Hodgkin's lymphoma. We report a case of 48-year-old male who presented a clinically benign swelling in the right anterior palatal region since last 2 months. Radiographic evaluation showed no bone loss in palatal area. Histological and radiological examination was in favor of a peripheral reactive lesion like pyogenic granuloma or a benign salivary gland tumor. Immunohistochemistry confirmed the diagnosis of anaplastic lymphoma kinase-negative (ALK(−)) ALCL. Further laboratory tests ELISA for human immunodeficiency virus (HIV) and CD4 cell count was done which showed positivity for HIV. To the best of our knowledge, it is the first case of ALK(−) ALCL in the hard palate presenting as the first clinical manifestation of acquired immune deficiency syndrome.